2010
DOI: 10.1186/1475-2859-9-98
|View full text |Cite
|
Sign up to set email alerts
|

High yield expression of leptospirosis vaccine candidates LigA and LipL32 in the methylotrophic yeast Pichia pastoris

Abstract: BackgroundLeptospirosis, a zoonosis caused by Leptospira spp., is recognized as an emergent infectious disease. Due to the lack of adequate diagnostic tools, vaccines are an attractive intervention strategy. Recombinant proteins produced in Escherichia coli have demonstrated promising results, albeit with variable efficacy. Pichia pastoris is an alternative host with several advantages for the production of recombinant proteins.ResultsThe vaccine candidates LigANI and LipL32 were cloned and expressed in P. pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
(39 reference statements)
0
12
1
1
Order By: Relevance
“…The rLipL32 was expressed with a His-Tag at the C-terminus in E. coli under the control of an IPTG-induced T7 promoter. SDS-PAGE analysis showed that the rLipL32 expressed was approximately 40 kDa in size, which differs from what has been reported in the literature (9,19,20,21,22,23). The synthetic lipl32 gene in this study was designed without its own start codon (ATG), and the expression of rLipL32 was initiated by the start codon from the pET22b expression vector, thus causing an increase in the molecular weight of the rLipL32 protein.…”
Section: Discussioncontrasting
confidence: 80%
“…The rLipL32 was expressed with a His-Tag at the C-terminus in E. coli under the control of an IPTG-induced T7 promoter. SDS-PAGE analysis showed that the rLipL32 expressed was approximately 40 kDa in size, which differs from what has been reported in the literature (9,19,20,21,22,23). The synthetic lipl32 gene in this study was designed without its own start codon (ATG), and the expression of rLipL32 was initiated by the start codon from the pET22b expression vector, thus causing an increase in the molecular weight of the rLipL32 protein.…”
Section: Discussioncontrasting
confidence: 80%
“…O sistema de expressão P. pastoris que foi utilizado para a expressão da proteína EMA-2 de T. equi, proporciona um aumento na produção da proteína, se comparada ao sistema E. coli, pois as proteínas são secretadas para o meio facilitando sua purifi cação (HARTWIG et al, 2010).…”
Section: Resultsunclassified
“…These results demonstrated that ELISA developed here could be used as a screening test before confirmation by the MAT. The large-scale production of proteins with potential diagnostic value is important for the pharmaceutical, biomedical and biotechnological applications (Cos et al 2006;Hartwig et al 2010). An efficient secretion system is of great interest since these proteins may be easily recovered from the culture supernatant and maintain the conformational structure (Hartwig et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of rLipL32 MutS secretory phenotype was performed using the eukaryotic system based in P. pastoris, as described previously (Hartwig et al 2010). Briefly, a recombinant clone was grown in a baffled flask containing BMGY broth (1% yeast extract, 2% peptone, 1.34% yeast nitrogen base, 0.00004% biotin, 1 % glycerol, 100 mM potassium phosphate and 2 % agar, pH 6.0).…”
Section: Production Of Rlipl32mentioning
confidence: 99%
See 1 more Smart Citation